DEXAMETHASONE ANALYSIS ON SIX BRANDS OF PACKAGED HERBAL MEDICINE USING THIN LAYER CHROMATOGRAPHY METHOD - Fitria, Faizatul; Arifah, Farida Noor; Lukis, Prima Agusti; Rahadi, Anisa Fajduani; Hidayat, Fahmi (Molluca Journal of Chemistry Education (MJoCE), 2024)
ABSTRACT Herbal medicine is used for generations because of its safety and free from adverse side effects, but the healing process takes a long time. This is the background of herbal medicine manufacturers to improve their performance by adding dexamethasone compounds. This compound is a synthesis of corticosteroid hormones whose use must be under the supervision of a doctor because it has side effects of cardiovascular disease, Cushing's syndrome, osteoporosis, hypertension, gastrointestinal ulcers, infections, and cataracts. The presence of this compound can be detected using the Thin Layer Chromatography method by comparing the Rf value of the sample with the standard solution of dexamethasone. The eluents used are methanol, ethyl acetate, and toluene with a ratio of 1:45:55. This method was used to detect dexamethasone content in six samples of packaged herbs circulating in the Mojokerto region, East Java province. Of the six samples analyzed, five of them showed positive results, namely samples A, B, C, D and F with a difference in the Rf value of the sample and standard of each 0.01; 0.01; 0.00; 0.00; and 0.02. Sample E does not contain dexamethasone indicated by the difference in the sample's Rf value against the 0.5 standard. Keywords: Herbal medicine, herbal packaging, dexamethasone, corticosteroids, Thin Layer Chromatography (TLC).